How to keep your children safe: a guide for parents - Vissing, Yvonne Marie (University Press of New England, 2006)
Are kids safe? -- How safe is day care? -- How safe are nannies and au pairs? -- Child care by family and friends : relative safety -- Abuse of children in religious organizations -- "On my honor" : abuse in scouts and civic organizations -- Recreational safety -- How safe are kids at camp? -- Sports : more than just a game -- Transportation safety -- Safety at school -- Conclusion